E-Catalogue Berbasis Android - Rahma Annissa; Evi Yulianti (Jurnal Informatika Global)
ABSTRACTMinimarket Murah Meriah is a low-cost minimarket that exists in Palembang. Minimarket Murah Meriah distributes its products through offline media with brochures and banners as a means of product promotion.  In the modern era of mobile devices is growing very rapidly and also the evolution of mobile devices increases with the number of mobile platform applications. One of the most developed so far is Android. With the rapid development of information technology, a business can improve performance and improve the quality of its business by providing convenience and convenience for customers, without spending large costs to promote a product. To overcome this problem, researchers need a study to create a cellular information system that can be utilized by Minimarket Murah Meriah to build a low-cost minimarket E-catalog product so it is necessary to do a phase analysis, design phase The system uses UML, namely the Use Case Diagram, Activity Diagram, Class Diagram, Sequence Diagram) and finally the testing phase testing program, system testing (Black Box Testing and White Box Testing) and implementation. From the analysis and design of the system, a mobile information system can be made, namely an Android-based E-catalog that can be exploited by minimarkets in Palembang. The catalog application is designed with a simple and user-friendly design to facilitate its use. E-catalog will help the course of promotional activities. Besides, as an innovation promotion for other sellers, there is no need to use print media such as brochures or banner.Keywords : E-Catalog, Android, MinimarketABSTRAKMinimarket Murah Meriah adalah minimarket murah yang ada di Palembang. Minimarket Murah Meriah mendistribusikan produknya melalui media offline dengan brosur dan spanduk sebagai sarana promosi produk. Di era modern perangkat seluler berkembang sangat pesat dan juga evolusi perangkat seluler meningkat seiring dengan jumlah aplikasi platform seluler. Salah satu yang paling berkembang sejauh ini adalah Android. Dengan pesatnya perkembangan teknologi informasi, sebuah bisnis dapat meningkatkan kinerja dan meningkatkan kualitas bisnisnya dengan memberikan kemudahan dan kemudahan bagi pelanggan, tanpa mengeluarkan biaya besar untuk mempromosikan suatu produk. Untuk mengatasi masalah ini, peneliti memerlukan studi untuk membuat sistem informasi seluler yang dapat dimanfaatkan oleh Minimarket Murah Meriah untuk membangun produk E-katalog minimarket murah sehingga perlu melakukan fase analisis, tahap desain Sistem menggunakan UML , yaitu Use Case Diagram, Activity Diagram, Class Diagram, Sequence Diagram) dan akhirnya program pengujian tahap pengujian, pengujian sistem (Black Box Testing dan White Box Testing) dan implementasi. Dari analisis dan desain sistem, sistem informasi mobile dapat dibuat, yaitu E-katalog berbasis Android yang dapat dieksploitasi oleh minimarket di Palembang. Aplikasi katalog dirancang dengan desain yang sederhana dan ramah pengguna untuk memfasilitasi penggunaannya. E-katalog akan membantu jalannya kegiatan promosi. Selain itu, sebagai promosi inovasi untuk penjual lain, tidak perlu menggunakan media cetak seperti brosur atau spanduk.Kata kunci : E-Catalog, Android, Minimarket